1989
DOI: 10.1128/mcb.9.12.5289-5297.1989
|View full text |Cite
|
Sign up to set email alerts
|

Discrete Mutations Introduced in the Predicted Nucleotide-Binding Sites of the mdr1 Gene Abolish Its Ability To Confer Multidrug Resistance

Abstract: In cells stably transfected and overexpressing the mouse mdr1 gene, multidrug resistance is associated with an increased ATP-dependent drug efflux. Analysis of the predicted amino acid sequence of the MDR1 protein revealed the presence of two putative nucleotide-binding sites (NBS). To assess the functional importance of these NBS in the overall drug resistance phenotype conferred by mdr1, we introduced amino acid substitutions in the core consensus sequence for nucleotide binding, GXGKST. Mutants bearing the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

1991
1991
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 36 publications
0
1
1
Order By: Relevance
“…In this regard, it is notable that the sequence homology between NBD1 and NBD2 in CFTR is much less 0-0 CPT-cAMP than for other proteins of similar overall structure with duplicate NBDs. Interestingly, the results discussed above contrast with those of similar studies on the NBDs of MDR, in which equivalent mutations in the two domains generally have the same effect on function (2).…”
Section: Discussioncontrasting
confidence: 74%
“…In this regard, it is notable that the sequence homology between NBD1 and NBD2 in CFTR is much less 0-0 CPT-cAMP than for other proteins of similar overall structure with duplicate NBDs. Interestingly, the results discussed above contrast with those of similar studies on the NBDs of MDR, in which equivalent mutations in the two domains generally have the same effect on function (2).…”
Section: Discussioncontrasting
confidence: 74%
“…This switch from the inward- to the outward-facing orientation results in a redistribution of the drug-binding residues with more of these binding regions facing the extracellular side [ 79 ]. ATP plays an essential role in the stabilisation of this conformation and several studies have suggested an association between the ATPase activity of PGP and substrate efflux leading to drug resistance [ 87 , 88 , 89 , 90 , 91 ]. It has been reported that PGP can have lower drug affinity in the presence of ATP [ 92 , 93 , 94 , 95 , 96 ], while the use of the ATP analogue, adenylylimidodiphosphate, results in drug efflux [ 97 ].…”
Section: The Structure Of P-glycoproteinmentioning
confidence: 99%